Study of Interaction Between N-Aralkylsalicylaldimines and Halides of Cadmium(II) and Mercury (II) - Nath, Rabinder; Bhatnagar, R.P. (Asian Journal of Chemistry, 2010)
The interaction between N-aralkylsalicylaldimines and halides of cadmium (II) and mercury(II) in dry methanol /ethanol yielded a series of interesting complexes conforming with 1 : 1 or 1 : 2 metal halide ligand stoichiometry, depending upon the nature of substituents on the aldehyde moiety and the molecular size of metal halides. Probable structures have been proposed for the resulting complex species based on analytical and spectroscopical evidences. Reaction between mercuric chlorides and ligands in 95% aqueous ethanol, on the other hand, led to the decomposition of the latter with simultaneous formation of dimeric metal amine complexes of 1:1 stoichiometric ratio.